Serial Monitoring of Immune Markers Being Represented Regulatory T Cell/T Helper 17 Cell Ratio: Indicating Tolerance for Tapering Immunosuppression after Liver Transplantation - Jhun, JooYeon; Lee, Seung Hoon; Lee, Soon Kyu; Kim, Hee Yeon; Jung, Eun Sun; Kim, Dong Goo; Choi, JeongWon; Bae, Si Hyun; Yoon, Seung Kew; Chung, Byung Ha; Yang, Chul Woo; Cho, Mi-La; et al. (Frontiers in Immunology, 2018)
Recipients of liver transplantation (LT) require long-term immunosuppressive drug treatment, but lifelong immunosuppressive treatment has severe side effects. It is known that some LT recipients develop immune tolerance, and although the development of such operational tolerance should allow a decrease in the burden of immunosuppressive drug treatment, the factors that indicate operational tolerance are not clear. This study aimed to monitor immunological markers over time in LT recipients to identify those markers indicating the development of operational tolerance. We performed a prospective pilot study measuring immune markers including the ratio of regulatory T (Treg) and helper T (Th) 17 cells in peripheral blood in the 14 most immunologically stable patients among 70 clinically stable LT recipients. The doses of immunosuppressive drugs given to these 14 LT recipients were tapered over time, and they were monitored for immunological markers related to the development of immune tolerance. As the doses of immunosuppressive drugs were reduced, the Treg/Th17, Th1/Th17 and CD8/Th17 ratio in tolerant recipients was significantly increased compared with that in nontolerant recipients. These results suggest that monitoring of changes in the immune makers including Treg/Th17 ratio during tapering of immunosuppression may allow prediction of the development of tolerance.